The Kind of Transportation Used Between Home and School in Children and Perception of Urban Space: Case of Kirklareli - Merve GÜROĞLU AĞDAŞ (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The type of transportation used has an impact on the perception of urban space. For children, traveling by foot or cycling is an action beyond reaching a place. According to the “Spatial Planning Policy Framework” elementary school buildings should be planned in the service impact area which should be reached on foot by considering the distance of approximately 500 meters. However, today most of the children reach the school by vehicle because of the effect of urban sprawl. Most of cities do not have adequate regulations for walking and cycling. Traveling on foot and cycling has been adopted as an important research topic and country policy in developed countries, while in developing countries this issue cannot be attracted much attention. The aim of the study is to determine which type of transportation children use when going to school and its effect on the perception of urban space. To achieve this, surveys which include cognitive mapping, were conducted with 194 students who are in the 4th class. As a result, it was seen that most of the children wanted to make their school transportation by bicycle and on foot. The study has a unique value in terms of providing data.